Public Health in Developing Countries Challenges and Opportunities - Eze Anugwom, Edlyne; Awofeso, Niyi (IntechOpen, 2020)
Public health entails the use of models, technologies, experience and evidence derived through consumer participation, translational research and population sciences to protect and improve the health of the population. Enhancing public health is of significant importance to the development of a nation, particularly for developing countries where the health care system is underdeveloped, fragile or vulnerable.This book examines progress and challenges with regards to public health in developing countries in two parts: Part 1 "General and Crosscutting Issues in Public Health and Case Studies" and Part 2 "Country-Specific Issues in Public Health." For example, assuring equity for marginalized indigenous groups and other key populations entails the application of transdisciplinary interventions including legislation, advocacy, financing, empowerment and de-stigmatization. The diverse structural, political, economic, technological, geographical and social landscape of developing countries translates to unique public health challenges, infrastructure and implementation trajectories in addressing issues such as vector-borne diseases and intimate partner violence.This volume will be of interest to researchers, health ministry policy makers, public health professionals and non-governmental organizations whose work entails collaborations with public health systems of developing nations and regions.